INTRODUCTION LEARNING VIDEO DEVELOPMENT MICROSOFT WORD FOR ELEMENTARY SCHOOL STUDENTS - NOVIANA ANA NOVI (STKIP Singkawang, 2022)
This study aims to (1) produce a learning video product for the introduction of microsoft word ; and (2) describe the effectiveness of the introduction of microsoft word learning videos for elementary school students. This development research uses the ADDIE design model with five steps, namely: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The design in this study was validated by two instrument validators, two design validators, two media validators and two material validators with the overall product validation results showing very good results. The research data was obtained from the questionnaire instrument and the value of students' knowledge. This study involved 27 third grade students of SD Marie Joseph Pontianak with the results on the one-on-one test, small group test and overall field test which could be interpreted very well. The results of the one-on-one trial obtained an overall average of 3.31 (good), the results of the small group trial obtained an overall average of 3.15 (good), the results of the large group trial obtained an overall average of 3.08 (good ). The results of the test of the effectiveness of the microsoft word introduction learning video product for elementary school students, the results were obtained from the pretest and posttest data that had been collected. It is known that the average pretest score is 72.5 with 11 students achieving the KKM and 9 students not achieving the KKM. Then the average posttest score was 85 with the number of students who reached the KKM there were 17 people and those who did not reach the KKM were 3 people. Through these results it can also be concluded if there is an increase in the average value of 12.5. These data indicate that there is a significant completeness.